2019
DOI: 10.9770/jesi.2019.6.4(4)
|View full text |Cite
|
Sign up to set email alerts
|

Projection of enterprise survival rate in dynamics of regional economic sustainability: case study of Russia and the EU

Abstract: Discussing the problem of economic sustainability, we are in general deal with life cycles and economic activity. Factors causing dynamics in entrepreneurial ventures, their duration and process rate depend on environmental conditions, including institutional, market, infrastructure, and resource aspects. A cumulative impact of all of these factors appears at a specific level of enterprise survival, which becomes a universal characteristic of sustainable economy. Going from official statistics on business demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Empirical evidence was also provided by [76], who argued that new businesses promote innovation and facilitate the introduction of new technologies, which ultimately translates into an increase in the overall performance of the economy. Addressing the issue from the perspective of start-ups, [77] revealed that the establishment of a new enterprise (and, implicitly, the generation of new jobs) is one of the key factors influencing economic growth.…”
Section: Resultsmentioning
confidence: 99%
“…Empirical evidence was also provided by [76], who argued that new businesses promote innovation and facilitate the introduction of new technologies, which ultimately translates into an increase in the overall performance of the economy. Addressing the issue from the perspective of start-ups, [77] revealed that the establishment of a new enterprise (and, implicitly, the generation of new jobs) is one of the key factors influencing economic growth.…”
Section: Resultsmentioning
confidence: 99%
“…This feature is also supported by an analysis of business activity in the EU countries. In general, in countries with a low average enterprise survival rate, in the first year, there is a persisting low rating in almost all of the industries, assuming that trends in enterprise sustainability dynamics depend on an overall economic situation instead of specifics in a particular sector (Kuzmin, Vinogradova, Guseva, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…This is the reason why, in the present study, the profit is considered as the main indicator which takes into account the efficiency of management, ensuring the sustainability and development of the economic organizations. Another important element that should be taken into account, is to ensure its longterm stable development and building innovation (Pukala et al, 2018;Kuzmin et al 2019).…”
Section: Methodsmentioning
confidence: 99%